Magnolia arroyoana, a new name for Magnolia crassifolia (Magnoliaceae) - Molinari-Novoa, Eduardo Antonio (Phytotaxa, 2016)
Magnolia crassifolia Arroyo & Pérez in Arroyo et al. (2013: 501) is a South American species known only from the type collection, which comes from primary forest found in the Ecuadorian province of Zamora Chinchipe, near the Peruvian-Ecuadorian border. However, it is an illegitimate later homonym of M. crassifolia Göppert (1852: 277), a fossil taxon described on the basis of leaf impressions found in Silesia, Germany. Therefore, the south American species requires a new name (Art 6. 11 of the ICN, McNeill et al. 2012), which is proposed below.